Visual Representation of Photography on the Cover of Fiction Novels - Arsita, Adya (JOMANTARA, 2024)
As a visual sign, photography is considered to be the right mediun to represent an object with all its resemblance with the reality. The reality embedded in a photography is in line with the reliability of its audience who adhere to "seeing is believeing" or believing in seeing. On the other hand, carefully structured verbal signs in a storyline appear in a narrative medium, one of which is a novel. Most novels that are considered popular are then often adapted to the story of a big screen film and then the cover of the original novel is replaced with a photo work that is considered as a representation of the story in a film. This research will examine how photography becomes an instrument of visual representation in conveying the message of the content of fiction novels and finding out the imagery relationships constructed by both verbal and pictorial texts on the cover of novels. This study used descriptive qualitative methods that would describe the aspects and characteristics of a particular message through empirical interpretation. It is hoped that the results of this study will add to the discourse on the visual representation of photography that can effectively deliver the message of the story by representing the entire narrative in the novel with just one frame in the form of a novel cover.